Respostas

  • Usuário do Brainly
2014-07-09T21:59:54-03:00
X²-3=x-3/6
Primeiramente, multiplique tudo por 6
6x^2-18=6x-3
6x^2-6x-15=0
Formula de Baskara
delta = b^2 - 4.a.c = (-2)^2 - 4(2)(-5) = 44      raiz delta = 2.(raiz de 11)
x = (- b + - raiz delta)/2a
x1 = [3 + (2.raiz de 11)]/4
x2 = [3 - (2.raiz de 11)]/4
S = {[3 - (2.raiz de 11)]/4, [3 + (2.raiz de 11)]/4}
1 5 1
  • Usuário do Brainly
2014-07-10T01:03:32-03:00
 x^{2} -3= \frac{x-3}{6}

mmc=6

6 x^{2} - 18=x-3

6 x^{2} -x-15=0

Δ=b²-4ac

Δ=1+360
Δ=361
√Δ=19

x'= \frac{1+19}{12} = \frac{20}{12} = \frac{5}{3}

x"= \frac{1-19}{12} = \frac{-18}{12} = \frac{-3}{2}

S={{ \frac{-3}{2} , \frac{5}{3} }}
1 5 1